(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The study aimed at investigating the relationship between substance abuse counseling and behavioural adjustments among university students in Uasin Gishu County. The study was anchored on Social Learning Theory by Albert Bandura (Bandura, 1977). The study used mixed method and phenomenological design. The target population comprised of 85,000students and 10 counselors drawn from six universities in Uasin Gishu County. Simple random sampling was used to draw a sample of 323 students while purposive sampling was used to select four counselors and three universities. This study used questionnaires and in-depth interviews guide to collect data. Qualitative data were transcribed and analyzed through themes derived from the research questions. Quantitative data was analyzed using SPSS version 26.0 and presented into frequencies, percentages, mean and standard deviations. To test the hypotheses, the researcher used ANOVA to determine whether there is a relationship that exists between the variables. From the findings it was established that substance abuse counseling (F (21, 178) =3.089, p=0.00) significantly influenced behavioural adjustments of students. The findings of the study may be useful to the community, institutions of higher learning and the society. The study recommended that there was need for dedicated efforts aimed at assessing the types of psychological counseling interventions available, their accessibility, and the level of awareness among students in Uasin Gishu County universities.